Biological environment-friendly rubber composition for outsoles of snow boots and preparation method of biological environment-friendly rubber composition

By using modified cellulose powder in the soles of snow boots, the problem of reducing flexibility of carbon black fillers dependent on fossil resources and rubber under low temperature conditions in the prior art is solved, and excellent anti-slip, wear resistance and low temperature performance are achieved, achieving the goal of bio-environmental protection.

CN119638853APending Publication Date: 2025-03-18XINXING JIHUA (BEIJING) MATERIAL TECH RES INST CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411913724.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The carbon black filler of existing snow boot soles relies on non-renewable fossil resources, and the flexibility of rubber is reduced under low temperature conditions, resulting in poor anti-slip effect and insufficient wear resistance.

Method used

Using bio-environmentally friendly rubber-modified cellulose powder, a rubber composition with excellent anti-slip, wear resistance and low temperature properties were prepared by dispersing cellulose formate in an aqueous solution of AlCl3/ZnCl2 and gas fumigating and vacuum drying.

Benefits of technology

The anti-slip performance, wear resistance and low-temperature performance of rubber soles is improved, and the dependence on fossil resources is reduced, and the goal of bio-environmental protection is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206353980000191
    Figure BDA0005206353980000191
  • Figure BDA0005206353980000201
    Figure BDA0005206353980000201
  • Figure DA00052063539838916841
    Figure DA00052063539838916841
Patent Text Reader

Abstract

The invention discloses a biological environment-friendly rubber composition for outsoles of snow boots and a preparation method of the biological environment-friendly rubber composition. The biological environment-friendly rubber composition for the snow boot outsole adopts modified cellulose powder as a rubber reinforcing material, and a preparation method of the modified cellulose powder comprises the following steps: S1, dispersing cellulose formate in a binary inorganic salt system composed of AlCl3, ZnCl2 and water to obtain a cellulose formate aqueous dispersion; s2, dropwise adding a coupling agent solution into the cellulose formate aqueous dispersion, and heating to obtain a cellulose formate-coupling agent dispersion; s3, the cellulose formate-coupling agent dispersion liquid is placed in a coagulating bath of deionized water for gas fumigation, and regenerated cellulose hydrogel is obtained; and S4, performing vacuum treatment on the regenerated cellulose hydrogel, and then performing freezing and vacuum drying in sequence to obtain the rubber modified cellulose powder. The rubber composition disclosed by the invention is biological and environment-friendly, and the prepared sole has excellent non-slip performance, wear resistance and rubber low-temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of shoemaking, and in particular to a biological and environmentally friendly rubber composition for snow boot outsoles and a preparation method thereof. Background Art

[0002] Affected by the extremely low temperature, rain, snow and freezing weather, snow boots have become one of the most commonly used wear items in winter, which has a good warming function. With the improvement of the quality of life, people are no longer satisfied with the most basic warming function of snow boots, which requires the upgrading and transformation of traditional snow boots manufacturing technology, especially the sole technology.

[0003] People wear snow boots to walk on icy roads and snowy roads (hereinafter referred to as "ice and snow roads"), so they are required to have a higher grip on ice and snow roads. The sole materials of common snow boots include plastic soles, foam soles, rubber soles, foamed soles, etc. Among them, rubber soles are widely used for their anti-skid and wear-resistant properties. However, there are still the following problems with rubber soles: first, the most commonly used filler in the sole manufacturing process is carbon black, and the raw materials for preparing carbon black are mainly carbon black, natural gas and coal tar, and the production raw materials are fossil resources, which are non-renewable resources. Under the premise of ensuring wear resistance, it is necessary to develop new environmentally friendly materials for replacing or partially replacing carbon black to reduce carbon emissions. Secondly, the defects of rubber soles in dealing with rain, snow, and freezing weather, which are very easy to appear, are still worthy of attention. Thirdly, rubber shrinks and hardens at low temperatures, which reduces the flexibility of the sole and easily cracks, and the low temperature resistance of rubber soles needs to be further improved. Summary of the invention

[0004] The purpose of the present invention is to provide a bio-environmentally friendly rubber composition for snow boot outsoles and a preparation method. On the one hand, based on traditional rubber soles, the present invention further improves the anti-slip performance of the soles, and at the same time uses biomass reinforcing fillers to improve the wear resistance of the soles, and is a bio-environmentally friendly rubber composition; on the other hand, the present invention can also improve the low-temperature performance of rubber, ensure that the snow boots soles have flexibility at low temperatures, and improve wearing comfort and low-temperature friction performance.

[0005] In a first aspect, the present invention protects a method for preparing a rubber-modified cellulose powder for snow boot outsoles, comprising the following steps:

[0006] S1, dispersing cellulose formate in a binary inorganic salt system consisting of AlCl3, ZnCl2 and water to obtain an aqueous dispersion of cellulose formate;

[0007] S2, dropping the coupling agent solution into the aqueous dispersion of cellulose formate and heating it to obtain a cellulose formate-coupling agent dispersion;

[0008] S3, placing the cellulose formate-coupling agent dispersion in a coagulation bath of deionized water for fumigation to obtain a regenerated cellulose hydrogel;

[0009] S4, subjecting the regenerated cellulose hydrogel to vacuum treatment, and then sequentially freezing and vacuum drying to obtain the rubber-modified cellulose powder for the snow boot outsole.

[0010] In the above-mentioned method for preparing rubber-modified cellulose powder for snow boot outsoles, in step S1, the cellulose formate has a degree of substitution of formate groups on the cellulose molecules of 1.0 to 2.0, and a crystalline form of cellulose II; the degree of polymerization of the cellulose formate is 300 to 1000;

[0011] The cellulose in the cellulose formate is one or more of microcrystalline cellulose, cotton pulp, dissolving pulp, ascidian cellulose and bacterial cellulose;

[0012] In the binary inorganic salt system, Al 3+ :Zn 2+ : The molar ratio of H2O is (0.1):(0.9):(3.5-5.5), preferably 0.1:0.9:4;

[0013] The dispersion is carried out at 15 to 30° C.

[0014] The dispersion is ultrasonic dispersion, preferably ultrasonic dispersion for 0.3 to 3 hours;

[0015] Each 1g of cellulose formate is dispersed in 1000mL of binary inorganic salt system;

[0016] The coupling agent is a silane coupling agent, preferably one or a mixture of bis(3-ethoxysilylpropyl)tetrasulfide, bis(3-ethoxysilylpropyl)disulfide, 3-(trimethylsiloxane)-1-propanethiol;

[0017] The solvent of the coupling agent solution is one or a mixed solvent of ethanol, polypropylene glycol, ethyl acetate, butyl acetate and hexane;

[0018] The volume ratio of the coupling agent solution to the aqueous dispersion of cellulose formate is 1:10;

[0019] The heating temperature is 70° C. to 100° C., preferably 80° C., and the heating time is 1 to 10 hours, preferably 2 hours.

[0020] In the above-mentioned method for preparing the rubber-modified cellulose powder for snow boot outsoles, in step S3, the fumigation time is 2 to 6 hours;

[0021] The method further comprises the step of centrifuging and degassing the cellulose solution before gas fumigation;

[0022] The method comprises the step of washing the regenerated cellulose hydrogel with water after fumigation;

[0023] The vacuum treatment comprises: 1) vacuuming the cellulose regenerated hydrogel at room temperature to a vacuum degree of -0.05 to 0.05 MPa; 2) flushing nitrogen to normal pressure, and then vacuuming to a vacuum degree of -0.05 to -0.01 MPa at 0 to 5°C; 3) flushing nitrogen to normal pressure, and then vacuuming to a vacuum degree of -0.05 to -0.01 MPa at 0 to 5°C, and repeating the steps of flushing nitrogen and vacuuming in step 2) 3 to 4 times;

[0024] The freezing temperature is -24°C to -80°C, and the freezing time is 2 to 4 hours.

[0025] In a second aspect, the present invention protects the rubber-modified cellulose powder for snow boot outsoles obtained by any of the preparation methods described above.

[0026] In a third aspect, the present invention protects a rubber composition for snow boot outsoles, which is made of raw materials including the following components, in parts by weight: 20 to 100 parts of diene elastomer, 0 to 80 parts of polar elastomer, 50 to 120 parts of reinforcing filler, 2 to 40 parts of hydrocarbon resin, 5 to 60 parts of liquid plasticizer, 2 to 20 parts of silane coupling agent, 1.0 to 2.5 parts of vulcanizing agent, 1.0 to 2.5 parts of sulfonamide accelerator, 2 parts of aging protective agent, 1.5 parts of antioxidant and 2 parts of rubber accelerator;

[0027] The diene elastomer carries at least one SiOR-functional group, R being hydrogen or hydroxyl;

[0028] The polar elastomer comprises one or more of nitrile rubber, hydrogenated nitrile rubber, and carboxyl nitrile rubber;

[0029] The reinforcing filler comprises carbon black, SiO2 and the modified cellulose powder material described above;

[0030] The glass transition temperature of the hydrocarbon resin is ≥20°C.

[0031] In the above-mentioned rubber composition for snow boot outsoles, the diene elastomer is one or a mixture of two or more of polybutadiene rubber (BR), synthetic isoprene (IR), natural rubber (NR), and butadiene copolymer; the polybutadiene rubber is preferably a polybutadiene rubber having a cis-1,4-bond content greater than 90%; the butadiene copolymer is preferably a butadiene-styrene copolymer having a glass transition temperature of 0°C to -80°C, a styrene content of 5% to 60% by weight, a 1,2-bond molar content of 4% to 75% in the butadiene part, and a trans-1,4-bond molar content of 10% to 80%;

[0032] In the SiOR functional groups of the diene elastomer, R is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms; the diene elastomer is preferably a diene elastomer modified with SiOR functional groups at both ends;

[0033] The content of acrylonitrile in the molecular structure of the polar elastomer is greater than 25%;

[0034] In the reinforcing filler, the mass ratio of carbon black, SiO2 and the modified cellulose powder material is (2-10): (70-120): (5-30);

[0035] The silane coupling agent is at least a bifunctional organosilane or polyorganosiloxane, preferably a silane polysulfide of the following general formula:

[0036] ZA-SX-AZ(I)

[0037] In formula (I), x is an integer from 2 to 8 (preferably from 2 to 5); the A symbols, which are the same or different, identify a divalent hydrocarbon group (preferably a C1-C18 alkylene group or a C6-C12 arylene group, more particularly a C1-C10, especially a C1-C4, alkylene group, especially propylene); the Z symbols, which are the same or different, correspond to one of the following three formulae:

[0038]

[0039] in:

[0040] - R1 groups are substituted or unsubstituted and identical or different from each other and represent C1-C18 alkylene, C5-C18 cycloalkyl or C6-C12 arylene (preferably C1-C6 alkyl, cyclohexyl or phenyl, in particular C1-C4 alkyl, more in particular methyl and / or ethyl);

[0041] -R2 groups are substituted or unsubstituted and identical to or different from each other and represent C1-C18 alkoxy, C5-C18 cycloalkoxy or C6-C12 arylene (preferably C1-C8 alkoxy, C5-C8 cycloalkoxy groups, in particular C1-C4 alkoxy, more in particular methoxy and / or ethoxy).

[0042] In the above-mentioned rubber composition for snow boot outsoles, the weight ratio of the hydrocarbon resin to the liquid plasticizer is 1:5 to 5:1, preferably 1:4 to 4:1;

[0043] The total mass fraction of the hydrocarbon resin and the liquid plasticizer is 10 to 80 parts;

[0044] The glass transition temperature of the hydrocarbon resin is ≥25°C, preferably 30°C to 100°C, more preferably 30°C to 95°C;

[0045] The number average molar mass Mn of the hydrocarbon resin is 400 to 2000 g / mol, preferably 500 to 1500 mol / g;

[0046] The molecular weight distribution D of the hydrocarbon resin is less than 3, preferably less than 2;

[0047] The glass transition temperature of the liquid plasticizer is below -20°C, more preferably below -40°C;

[0048] The liquid plasticizer is selected from one or more of liquid diene polymers, polyolefin oils, paraffin oils, aromatic extract oils, shallow extraction oils, treated aromatic extract oils, rubber aromatic oils, mineral oils, vegetable oils, ester plasticizers, ether plasticizers, phosphate plasticizers, sulfonate plasticizers, and carboxylate plasticizers;

[0049] The sulfonate plasticizer is preferably one or more of alkyl phenyl sulfonate, sodium benzene sulfinate, and 1,4-butane sultone;

[0050] The phosphate plasticizer preferably contains between 12 and 30 carbon atoms, more preferably trioctyl phosphate;

[0051] The carboxylic acid ester plasticizer is preferably one or more of trimellitate, triglyceride, adipate, azelaic acid ester, sebacate, and dioctyl phthalate;

[0052] The vulcanizing agent is a crosslinking system based on sulfur and sulfur donor and / or peroxide and / or bismaleimide, preferably sulfur;

[0053] The sulfenamide type accelerator is selected from one or more of N-dicyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, N,N-dicyclohexyl-2-benzothiazole sulfenamide, and N-oxydiethylene-2-benzothiazole sulfenamide;

[0054] The aging protective agent is one or more of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-xylyl-p-phenylenediamine, N-(1,4-dimethylpentyl)-N'-phenyl-p-phenylenediamine, and N-(1-methylhexyl)-N'-phenyl-p-phenylenediamine;

[0055] The antioxidant is rubber protective wax;

[0056] The rubber accelerator is one or more of diphenylguanidine and tetrabenzylthiuram disulfide.

[0057] In a fourth aspect, the present invention provides a method for preparing the rubber composition for snow boot outsoles as described in any one of the above items, comprising the following steps:

[0058] 1) premixing the diene elastomer, the polar elastomer, the reinforcing filler, the silane coupling agent, the hydrocarbon resin, the liquid plasticizer, the aging protective agent and the antioxidant in a closed container, collecting and cooling the obtained mixture;

[0059] 2) adding the vulcanizing agent, the sulfonamide type accelerator and the rubber accelerator into the mixture for mixing and cross-linking to obtain the rubber composition.

[0060] In the method for preparing the rubber composition for snow boot outsoles, the premix is ​​heated to a maximum temperature of 110°C to 190°C in the container, and then stopped for cooling, preferably 130°C to 180°C, and the heating time of the premix is ​​3 to 15 minutes;

[0061] The mixing and cross-linking is performed by heating to below 110° C., preferably 40° C. to 100° C., and the heating time for the mixing and cross-linking is 5 to 12 minutes.

[0062] In a fifth aspect, the present invention provides a snow boot outsole, which is made of the rubber composition for snow boot outsole described in any one of the above items or the rubber composition prepared by any one of the preparation methods described in the above items.

[0063] In particular, the bio-environmentally friendly rubber composition of the present invention is intended to be assembled on snow boots worn by users, including hiking snow boots, skiing snow boots, urban snow boots, work snow boots, children's snow boots, and military snow boots.

[0064] The present invention has the following beneficial effects:

[0065] (1) In the preparation process of the modified cellulose powder of the present invention, the AlCl3 / ZnCl2·4H2O solvent system is used to dissolve cellulose formate, and this method is carried out at room temperature, which has little degradation of cellulose formate and is beneficial to subsequent solvent recovery and material construction.

[0066] (2) The modified cellulose powder prepared by the method of the present invention is easy to be evenly dispersed in rubber and has a strong interface effect with the rubber. When the modified cellulose powder is used as a reinforcing filler for rubber, the prepared rubber has excellent mechanical properties and good wear resistance.

[0067] (3) The present invention adopts the outsole snow boot formulation technology of a diene rubber composition with a low glass transition temperature Tg: the combined use of certain functional diene elastomers, cellulose reinforced fillers and a specific plasticizer system can improve the grip performance of the sole in dry and wet conditions.

[0068] In summary, the present invention adopts modified cellulose powder as a reinforcing material for rubber, and combines it with components such as a diene elastomer and a plasticizer system to prepare a rubber material. The obtained rubber sole has excellent anti-slip performance, wear resistance, and low-temperature performance of rubber. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 The structure of cellulose.

[0070] Figure 2 Schematic diagram of the mechanism of cellulose dissolving in AlCl3 / ZnCl2·4H2O at room temperature.

[0071] Figure 3 The DP changes of different celluloses before and after dissolution in different systems in Example 1 of the present invention and Comparative Example 1 are shown, wherein MCC represents microcrystalline cellulose, BWP represents bleached wood pulp, and CLP represents cotton linter pulp.

[0072] Figure 4 The present invention is a process flow chart for preparing the rubber composition. DETAILED DESCRIPTION

[0073] In order to find environmentally friendly materials for replacing or partially replacing carbon black, the present invention attempts to use cellulose as a biological reinforcing filler to replace part of the carbon black in the rubber outsole. Cellulose is the most abundant renewable resource in nature and a typical natural organic polymer compound. Using cellulose to prepare environmentally friendly rubber can reduce carbon emissions.

[0074] Cellulose is a linear polymer compound formed by β-pyranose glucose linked to each other by β-1,4 glycosidic bonds. It is composed of three elements: carbon (44%), hydrogen (6.17%), and oxygen (49.39%). Its chemical structure formula is (C6H 10 O5) n (n is the degree of polymerization), and the molecular weight is about 50,000 to 2,500,000 (molecular weight = 162n). The cellulose molecular chain has directionality, with one end having reducing properties (C1, the first segment hemiacetal structure) and the other end having no reducing properties (C4, the terminal group).

[0075] Cellulose is composed of alternating crystalline and amorphous regions. There are many hydrogen bonds between the crystalline regions. The hydrogen bond structure is as follows: Figure 1As shown in the figure, its molecular arrangement is regular and orderly, and the structure is compact; the amorphous region has less hydrogen bonding, the molecular arrangement is disordered, and there is a gradual transition between the crystalline region and the amorphous region. Due to the presence of a large number of hydroxyl groups, cellulose can easily form intramolecular and intermolecular hydrogen bonds, further forming its supramolecular structure. The supramolecular structure of cellulose, its degree of polymerization and hydrogen bonds have a huge impact on the physical and chemical properties of cellulose and its applications. The hydrogen bonds within the cellulose molecules make the fibers rigid, straight and hard; the hydrogen bonds between the molecules make the cellulose molecules form fibrils and then microfibrils. The strong hydrogen bonding of cellulose makes it extremely difficult to disperse in diene rubbers, restricting cellulose as a reinforcing agent to reinforce rubber, and causing the mechanical strength of the composite materials prepared by it to be far lower than that of the rubber composites prepared by traditional fillers. The dissolution of cellulose is one of the key steps that are indispensable for the deep processing, functional modification and construction of new materials of cellulose raw materials. However, due to the highly regular crystal sequence and supramolecular structure of cellulose, it cannot melt or dissolve in water or conventional solvents, which greatly limits the development and high-value utilization of cellulose-based materials. Moreover, most solvent systems have the problems of high price, toxicity and environmental threat, complex dissolution process, low dissolution efficiency, difficulty in solvent recovery and high energy consumption. In view of this, the present invention first needs to solve the problem that the existing cellulose is difficult to disperse in rubber and the interface between rubber molecules and cellulose materials is weak.

[0076] The present invention provides a method for preparing a rubber-modified cellulose powder for snow boot outsole, comprising the following steps: S1, dispersing cellulose formate in a binary inorganic salt system consisting of AlCl3, ZnCl2 and water to obtain an aqueous dispersion of cellulose formate; S2, dropping a coupling agent solution into the aqueous dispersion of cellulose formate for heating to obtain a cellulose formate-coupling agent dispersion; S3, placing the cellulose formate-coupling agent dispersion in a coagulation bath of deionized water for fumigation to obtain a regenerated cellulose hydrogel; S4, vacuum-treating the regenerated cellulose hydrogel, and then freezing and vacuum-drying in sequence to obtain the rubber-modified cellulose powder for snow boot outsole. Based on the above preparation method, the modified cellulose powder prepared by the method of the present invention is easy to be evenly dispersed in rubber and has a strong interface effect with the rubber. When the modified cellulose powder is used as a reinforcing filler for rubber, the prepared rubber has excellent mechanical properties and good wear resistance.

[0077] In at least one embodiment of the present invention, in step S1, the cellulose formate is prepared from cellulose (structured as Figure 1cellulose formate) is dissolved in a formic acid solution, and each glucose group in the cellulose macromolecule contains three alcoholic hydroxyl groups, which undergo a protonation reaction to generate the corresponding cellulose formate. Preferably, in the cellulose formate, the degree of substitution of the formate group is 1.0 to 2.0, and the crystal form is cellulose type II; the cellulose formate can be dissolved in formic acid, dimethyl sulfoxide, pyridine, N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide; the degree of polymerization of the cellulose formate is 300 to 1000; the cellulose can be microcrystalline cellulose, cotton pulp, dissolving pulp, sea squirt cellulose or bacterial cellulose.

[0078] In at least one embodiment of the present invention, in step S1, in the binary inorganic salt system, Al 3+ :Zn 2+ The molar ratio of H2O is (0.1):(0.9):(3.5-5.5), preferably 0.1:0.9:4. Figure 2 The dissolution mechanism of cellulose formate is shown in the preferred AlCl3 / ZnCl2·4H2O solvent system. 3+ and Zn 2+ It is only combined with 4 water molecules and is in an unsaturated state. 2+ In comparison, Al 3+ With a smaller ionic radius and higher charge density, it has a stronger attraction to water molecules and attacks and destroys the hydrogen bonds between and within cellulose fiber molecules, followed by a large amount of unsaturated hydrated Zn 2+ It enters the relatively loose structure of cellulose and synergistically destroys some of the hydrogen bonds of cellulose, causing more hydrogen bonds to further break, making the cellulose chains evenly dispersed in the aqueous solution to form a clear and transparent solution.

[0079] At present, the main solvents for cellulose include alkaline urine system, NMMO, LiCl / DMAc, ionic liquid system, quaternary ammonium salt solvent system and inorganic salt solvent system. However, the current solvent systems all have certain shortcomings, such as unstable solvents, complex processes, high costs, and immature recovery technologies. The alkaline urine system can only dissolve cellulose with lower DP (DP≤600) and needs to be dissolved at low temperatures (about -15°C). The LiCl / DMAc solvent system requires a long time (24 hours) and a higher temperature (≥100°C) to dissolve cellulose (DP<1800). The NMMO solvent itself is unstable. Although it can dissolve cellulose with high DP (DP~2000), it needs to be dissolved at a higher temperature (100°C). Although some ionic liquids can dissolve cellulose at room temperature, the solvent cost is high, the viscosity is high, the synthesis is complex, and the relevant biological toxicity data is incomplete. The present invention adopts the binary inorganic salt system, which can make the cellulose chain evenly dispersed in the aqueous solution at room temperature, which is convenient for solvent recovery.

[0080] The inventors investigated the DP changes of cellulose before and after dissolution in different dispersion systems in practice, and specifically compared the DP changes of different celluloses before and after dissolution in AlCl3 / ZnCl2·4H2O (with the same composition as in Example 1) and ZnCl2·4H2O systems. The experimental results are as follows: Figure 3 As shown in Figure 2, cellulose DP (degree of polymerization) is a very important factor in the process of cellulose dissolution. Figure 3 The dissolution and regeneration of microcrystalline cellulose MCC (DP, ~190), bleached wood pulp BWP (DP, ~1000), and cotton linter pulp CLP (DP, 2000 ~ 2200) in different inorganic salt aqueous solutions were compared. The results showed that cellulose was slightly degraded in AlCl3 / ZnCl2·4H2O. The main reason is that the dissolution process does not require heating and can effectively dissolve cellulose at room temperature and in a short time.

[0081] In at least one embodiment of the present invention, in step S1, the dispersion is carried out at 15-30°C; the dispersion is specifically ultrasonic dispersion, preferably ultrasonic dispersion for 0.3-3h. Since the dispersion is carried out at room temperature, the degradation of cellulose formate is small, which is beneficial to the subsequent solvent recovery and material construction. The recyclability and reuse performance of the solvent is particularly important for industrial application scale and sustainable development. The recovery and reuse of the AlCl3 / ZnCl2 water solvent system used in the present invention is achieved by simple deionized water regeneration, washing and rotary evaporation, which can realize closed-loop recycling and will not burden the environment. The specific steps are as follows: (1) deionized water regeneration washing: slowly add deionized water to the used AlCl3 / ZnCl2 solvent system, gently stir for about 10-30 minutes to dissolve the impurities in the deionized water, separate the impurities by decantation or a separatory funnel, and repeat the above steps 2-3 times, wherein the volume of deionized water used each time can be added according to 1-2 times of the solvent system; (2) rotary evaporation: pour the washed AlCl3 / ZnCl2 solvent system into a rotary evaporator, set the rotation speed to 40-100 r / min, and the temperature to 60-90°C. After rotary evaporation, collect the concentrated AlCl3 / ZnCl2 solvent system and seal it for subsequent use.

[0082] In at least one embodiment of the present invention, in step S1, 1 g of cellulose formate is dispersed in 1000 mL of a binary inorganic salt system, stirred evenly, and ultrasonicated for 2 hours to obtain an aqueous dispersion of cellulose formate; the solubility can be adjusted within a reasonable range. The molecular structure of the modified cellulose powder is grafted with metal ions Zn 2+ and Al 3+ .

[0083] In at least one embodiment of the present invention, the coupling agent is a silane coupling agent, such as bis(3-ethoxysilylpropyl)tetrasulfide having the formula [(C2H5O)3Si(CH2)3S2]2, abbreviated as TESPT, or bis(3-ethoxysilylpropyl)disulfide having the formula [(C2H5O)3Si(CH2)3S]2, abbreviated as TESPD, or 3-(trimethylsiloxane)-1-propanethiol having the formula (CH3O)3Si(CH2)3SH, abbreviated as MPS, or one or more mixtures thereof; the solvent of the coupling agent solution is ethanol, polypropanol; ethyl acetate, butyl acetate; hexane, or one or more mixed solvents thereof; the volume ratio of the coupling agent solution to the aqueous dispersion of cellulose formate can be adjusted according to the reaction requirements, preferably 1:10; the heating temperature is between 70°C and 100°C, preferably 80°C, and the heating time is 1 to 10h, preferably 2h. Specifically, in step S2, 6 g of coupling agent Si75 is added to 100 ml of ethanol, and after uniform mixing, an aqueous dispersion of cellulose formate is added dropwise, and the mixture is heated to 80° C. with stirring and reacted for 2 hours to obtain a cellulose formate-coupling agent dispersion; wherein the coupling agent serves as a modifier of cellulose formate.

[0084] In at least one embodiment of the present invention, in step S3, the method further comprises a step of centrifugally degassing the cellulose solution before gas fumigation. Centrifugal degassing can avoid gelation. Gelation is irreversible, causing the viscosity of the cellulose solution to increase and lose fluidity.

[0085] In at least one embodiment of the present invention, in step S3, the fumigation time is 2-6 hours, and the specific time depends on the thickness of the cellulose condensation and the gas concentration. Cellulose gel fumigation is mainly used for cross-linking and other reaction processes. If the fumigation time is too short, the gel cross-linking may not be complete, the mechanical properties of the prepared gel are poor, and the stability will also be affected. If the fumigation time is too long, the gel may be over-cross-linked, making it too hard and brittle, reducing elasticity, and even changing the chemical composition of the gel.

[0086] In at least one embodiment of the present invention, in step S3, the method comprises the step of washing the regenerated cellulose hydrogel after fumigation. The purpose of washing is mainly to remove unreacted reagents and reaction by-products. Some cross-linking agents or modifying agents are used during the fumigation process. For example, when glutaraldehyde is used for fumigation, unreacted toxic glutaraldehyde will remain in the gel after fumigation. Removing it by washing can ensure the safety of the cellulose gel during subsequent use.

[0087] In at least one embodiment of the present invention, in step S4, the vacuum treatment includes: 1) vacuuming the cellulose regenerated hydrogel at room temperature to a vacuum degree of -0.05 to 0.05 MPa; 2) flushing nitrogen to normal pressure, and then vacuuming to a vacuum degree of -0.05 to -0.01 MPa at 0 to 5°C; 3) flushing nitrogen to normal pressure, and then vacuuming to a vacuum degree of -0.05 to -0.01 MPa at 0 to 5°C, and repeating the steps of flushing nitrogen and vacuuming in step 2) 3-4 times). Among them, step 2) is mainly 0 to 5°C, and the temperature should not be too high to prevent the water in the hydrogel from evaporating rapidly, causing the hydrogel to dry or crack. Vacuuming can effectively remove bubbles in the hydrogel and allow part of the water in the gel to be initially removed under a low-pressure environment.

[0088] In at least one embodiment of the present invention, in step S4, the freezing is quick freezing with liquid nitrogen. The freezing temperature is -24°C to -80°C, and the time is 2 to 4 hours. For example, the freezing time is 2-4 hours, and the freezing temperature is -20°C. The longer the freezing time, the more fully the hydrogel is frozen.

[0089] In at least one embodiment of the present invention, in step S4, the vacuum drying includes: 1) quickly transferring the frozen sample to a vacuum freeze dryer; 2) turning on the vacuum pump to maintain a high vacuum inside the dryer, with the pressure generally below 5 mbar; 3) gradually increasing the temperature between 0-40°C to allow the ice to directly sublime into water vapor, which is then pumped away. The drying time is approximately 1-3 days, and the specific time depends on the amount of the sample and the performance of the freeze dryer, and finally a rubber-modified cellulose powder material is obtained.

[0090] In the second part, the present invention provides a rubber-modified cellulose powder for snow boot outsoles obtained by any of the above-mentioned preparation methods. The rubber-modified cellulose powder for snow boot outsoles can be used as a reinforcing filler for rubber to further improve the mechanical properties of the rubber composition.

[0091] The third part of the present invention provides a rubber composition for snow boot outsoles, which is made of raw materials including the following components in parts by weight: 20 to 100 parts of diene elastomer, 0 to 80 parts of polar elastomer, 50 to 120 parts of reinforcing filler, 2 to 40 parts of hydrocarbon resin, 5 to 60 parts of liquid plasticizer, 2 to 20 parts of silane coupling agent, 1.0 to 2.5 parts of sulfur, 1.0 to 2.5 parts of sulfonamide accelerator, 2 parts of aging protective agent, 1.5 parts of antioxidant and 2 parts of rubber accelerator;

[0092] The diene elastomer carries at least one SiOR-functional group, R being hydrogen or hydroxyl;

[0093] The polar elastomer comprises one or more of nitrile rubber, hydrogenated nitrile rubber, and carboxyl nitrile rubber;

[0094] The reinforcing filler comprises carbon black, SiO2 and the modified cellulose powder material described above;

[0095] The glass transition temperature of the hydrocarbon resin is ≥20°C.

[0096] Regarding the weight parts, as an example, it can be specifically confirmed by phr. For example, the rubber composition for the outsole of snow boots is made of the following raw materials, calculated by weight parts: diene elastomer 20-100 phr, polar elastomer 0-80 phr, reinforcing filler 50-120 phr, hydrocarbon resin 2-40 phr, liquid plasticizer 5-60 phr, silane coupling agent 2-20 phr, sulfur 1.0-2.5 phr, sulfenamide accelerator 1.0-2.5 phr, aging protective agent 2 phr, antioxidant 1.5 phr and rubber accelerator 2 phr.

[0097] Detailed description of the invention

[0098] Unless expressly stated otherwise, all percentages (%) shown in this specification are % by weight. The abbreviation "phr" stands for parts by weight per hundred parts of elastomer (or total elastomer if a species elastomer is present). All values ​​of glass transition temperature "Tg" are measured in a known manner by DSC (Differential Scanning Calorimetry) according to standard "ASTM D3418 (2021)".

[0099] I-1, Diene elastomer

[0100] “Diene elastomer” is understood in a known manner to mean one or more elastomers obtained at least partly (ie homopolymer or copolymer) from diene monomers (monomers carrying two carbon-carbon double bonds which may be conjugated or non-conjugated). Preferably, the diene elastomer is a polybutadiene (BR), in particular a polybutadiene having a cis-1,4-bond content greater than 90%, a synthetic isoprene (IR), a natural rubber (NR), a butadiene copolymer or a blend of these elastomers; more preferably, the diene elastomer is a butadiene-styrene copolymer (SBR) and a mixture of these copolymers; these suitable copolymers are in particular butadiene-styrene copolymers having a Tg (glass transition temperature Tg, measured according to standard ASTM D3418) between 0° C. and −80° C., a styrene content between 5% and 60% by weight, in particular between 10% and 50% by weight, a 1,2-bond content (mol %) of the butadiene portion between 4% and 75% and a trans-1,4-bond content (mol %) between 10% and 80%; wherein the diene elastomer carries at least one or more SiOR functional groups, R being hydrogen or a hydrocarbon radical, in particular an alkyl radical, preferably an alkyl radical having 1 to 12 carbon atoms, in particular a methyl or ethyl radical.

[0101] An essential feature of the rubber composition of the snow boot outsole according to the invention is that it comprises a first diene elastomer carrying at least one (i.e. one or more) SiOR functional group, R being hydrogen or a hydrocarbon radical, in particular an alkyl radical, preferably an alkyl radical having from 1 to 12 carbon atoms, in particular a methyl or ethyl radical. In the present application, the expression "SiOR functional group" is used to denote at least one SiOR functional group, i.e. one or more SiOR functional groups.

[0102] In general, the functional groups carried by the elastomer can be located on the elastomer molecular chain according to one of three possible configurations: as pendant groups along the elastomer chain, not at one end of the elastomer chain or within the actual elastomer chain (i.e. not at the end). The latter case occurs especially in elastomers functionalized by using functional coupling agents or star-branching agents.

[0103] In particular, the position of the SiOR functional group carried by the first diene elastomer may be sidelined along the elastomer chain, at one end of the elastomer chain or within the elastomer chain. In the case where the elastomer carries several SiOR functional groups, these are one or other of the structures described above.

[0104] According to a preferred embodiment of the invention, the first diene elastomer is predominantly in linear form, that is to say, if it contains star-branched or branched chains, these chains represent a small fraction by weight in the elastomer.

[0105] According to a preferred embodiment of the invention, the first diene elastomer is prepared by anionic polymerization.

[0106] According to one particular preferred embodiment, the first diene elastomer carries at least one (ie one or more) functional group of formula SiOH (R is hydrogen), known as “silanol” functional group.

[0107] Diene elastomers of this definition are known and are described, for example, in documents EP 0 778 311 B1, WO 2008 / 141702, WO 2006 / 050486, EP 0 877 047 B1 or EP 1 400 559 B1. The silanol functional groups SiOH are preferably located at the chain ends of the diene elastomers, in particular in the form of dimethylsilanol groups -SiMe2SiOH.

[0108] In a specific embodiment of the present invention, the diene elastomer is styrene-butadiene rubber (butadiene-styrene copolymer), wherein Tg is -65°C, the styrene content is 15%, the 1,2-bond content (mol %) of the butadiene part is 24%, and it is NS712 produced by Zeon Corporation, and the butadiene part is at the end of the elastomer chain, and both ends have silanol functional groups;

[0109] According to the present invention, the polar elastomer comprises one or more of nitrile rubber (NBR), hydrogenated nitrile rubber, and carboxyl nitrile rubber; wherein the polar elastomer has a relatively high acrylonitrile content, preferably more than 25%. In a specific embodiment of the present invention, the polar elastomer is nitrile rubber (acrylonitrile-butadiene copolymer), wherein the acrylonitrile content is 26-28%, and is NBR 1072 produced by Nandi Chemical Co., Ltd.

[0110] I-2, Reinforcement Materials

[0111] The reinforcing filler comprises carbon black, SiO2 and the modified cellulose powder material described above;

[0112] According to the present invention, the reinforcing filler includes any inorganic or mineral filler, regardless of its color and origin (natural or synthetic), which, relative to carbon black, can alone reinforce the rubber composition intended for the manufacture of the biological and environmentally friendly outsole of snow boots without the need for a method other than a coupling agent, and can also be described as being able to replace conventional carbon black in terms of reinforcing effect; such fillers are usually characterized in a known manner by the presence of hydroxyl groups (-OH) on their surfaces; wherein, siliceous mineral fillers, preferably silicon dioxide (SiO2), are particularly suitable as reinforcing fillers. The silicon dioxide used is any reinforcing silicon dioxide known to those skilled in the art, especially any precipitated silicon dioxide or pyrogenic silicon dioxide having a BET specific surface area and a CTAB specific surface area of ​​less than 450 square meters / gram, preferably 30 to 400 square meters / gram, and particularly preferably 60 to 300 square meters / gram. Among them, the weight proportion of carbon black ranges from 2 to 10 phr, white carbon black ranges from 70 to 120 phr, and modified cellulose powder ranges from 5 to 30 phr; the carbon black can be specifically Cabot carbon black N234; the SiO2 can be specifically Rhodia white carbon black Zeosil1165MP.

[0113] In order to couple the reinforcing inorganic filler to the diene elastomer, a coupling agent (or binder) is used in a known manner which is intended to provide a connection of satisfactory chemical and / or physical nature between the inorganic filler (the surface of its particles) and the diene elastomer. This coupling agent is at least bifunctional. In particular, at least bifunctional organosilanes or polyorganosiloxanes are used.

[0114] Use is made in particular of silane polysulfides, which are called "symmetrical" or "asymmetrical" depending on their specific structure, as described, for example, in applications WO 003 / 002648 and WO 03 / 002649.

[0115] The silane polysulfide corresponding to the following general formula is not limited to the following definition:

[0116] (I)ZAS X -AZ, where:

[0117] -x is an integer from 2 to 8 (preferably from 2 to 5);

[0118] -A symbols, which are the same or different, identify a divalent hydrocarbon group (preferably C1-C 18 Alkylene or C6-C 12 Arylene, more particularly C1-C 10 , especially C1-C4, alkylene, especially propylene);

[0119] -Z symbols, which are the same or different, correspond to one of the following three formulas:

[0120]

[0121] in:

[0122] -R 1 The groups are substituted or unsubstituted and are the same or different from each other, indicating that C1-C 18 Alkylene, C5-C 18 Cycloalkyl or C6-C 12 Arylene (preferably C1-C6 alkyl, cyclohexyl or phenyl, especially C1-C4 alkyl, more especially methyl and / or ethyl)

[0123] -R 2 The groups are substituted or unsubstituted and are the same or different from each other, indicating that C1-C 18 Alkoxy, C5-C 18 Cycloalkoxy or C6-C 12 Arylene (preferably C1-C8 alkoxy, C5-C8 cycloalkoxy, in particular C1-C4 alkoxy, more in particular methoxy and / or ethoxy).

[0124] For mixtures of alkoxysilane polysulfides in formula (I), especially commercially available mixtures, the average value of the "x" index is preferably between 2 and 5 parts, more preferably close to 4 parts, such as 4. However, the present invention can be advantageously carried out using alkoxysilane disulfides (X=2).

[0125] According to the present invention, the silane coupling agent is bis-[3-(triethoxysilyl)-propyl]-tetrasulfide (Si69-TESPT) or bis-[3-(triethoxysilyl)-propyl]-disulfide (Si69-TESPD). In particular, for example, bis(monoethoxydimethylsilylalkylpropyl)tetrasulfide described in patent application WO02 / 083782.

[0126] In a specific embodiment of the present invention, the silane coupling agent is silane coupling agent Si-69, the chemical name of which is bis-[γ-(triethoxysilyl)propyl] tetrasulfide, and the molecular formula is (H5C2O)3Si(CH2)3·S4·(CH2)3·Si(OC2H5) 3, That is, in the above formula (I), A represents -(CH2)3, and Z represents -Si(H5C2O) 3, That is R 2 The groups are all H5C2O-.

[0127] The content of the silane coupling agent is preferably between 2 and 20 phr, more preferably between 3 and 15 phr.

[0128] I-3, Plasticizing System

[0129] Based on the modified cellulose powder material, the present invention develops a snow boot formulation technology for the outsole of a diene rubber composition with a low glass transition temperature Tg. The combined use of the diene elastomer, cellulose reinforced filler and a specific plasticizer system (hydrocarbon resin and liquid plasticizer) can improve the grip performance of the sole in dry and wet states.

[0130] According to the present invention, the hydrocarbon resin and the liquid plasticizer together form a plasticizing system, and the total content A+B is greater than 20 phr. In a preferred embodiment of the present invention, the weight ratio of hydrocarbon resin A to liquid plasticizer B is between 1:5 and 5:1, that is, between 1:(0.2-5.0), preferably between 1:4 and 4:1, that is, between 1:(0.25-4.0).

[0131] In a preferred embodiment of the present invention, the weight fraction of the hydrocarbon resin is 2 to 40 phr, the weight fraction of the liquid plasticizer is 5 to 60 phr, and the total weight fraction of the hydrocarbon resin and the liquid plasticizer is 10 to 80 phr.

[0132] In a preferred embodiment of the present invention, the glass transition temperature of the hydrocarbon resin is above 25°C (especially between 30°C and 100°C), more preferably above 30°C (especially between 30°C and 95°C). The number average molar mass (Mn) of the hydrocarbon resin is between 400 and 2000 g / mol, preferably between 500 and 1500 mol / g. The molecular weight distribution (D) of the hydrocarbon resin is less than 3, preferably less than 2 (molecular weight distribution D=Mw / Mn, where Mw is the weight average molar mass and Mn is the number average molar mass). In a specific embodiment of the present invention, the hydrocarbon resin is a modified C5 / C9 copolymer resin produced by ExxonMobil, with the brand name OpperaTM PR 383, with a glass transition temperature of 53°C, a weight average molecular weight of 800-900 g / mol, and an aromaticity of 10%;

[0133] According to the present invention, the liquid plasticizer is liquid at 23°C, and its function is to soften the matrix by diluting the elastomer and reinforcing filler; its Tg is preferably below -20°C, more preferably below -40°C. In a preferred embodiment of the present invention, the liquid plasticizer is selected from liquid diene polymers, polyolefin oils, paraffin oils, aromatic extract oils, shallow extraction oils, treated aromatic extract oils, rubber aromatic oils, mineral oils, vegetable oils (such as soybean vegetable oil), ester plasticizers, ether plasticizers, phosphate plasticizers, sulfonate plasticizers and mixtures of these compounds. A more preferred embodiment is ester plasticizers, ether plasticizers, phosphate plasticizers, sulfonate plasticizers or mixtures of these compounds.

[0134] Preferred examples of the sulfonate plasticizer include phenyl alkylsulfonate, sodium benzenesulfinate, and 1,4-butane sultone.

[0135] As the phosphate plasticizer, for example, there are plasticizers containing between 12 and 30 carbon atoms, such as trioctyl phosphate.

[0136] As examples of plasticizers for carboxylic acid esters, the following compounds can be particularly preferred: trimellitate, triglyceride, adipate, azelaic acid, sebacate, dioctyl phthalate or a mixture of these compounds. Among the above-mentioned triesters, triglycerides can be particularly preferred, preferably triglycerides mainly (greater than 50% by weight, more preferably greater than 80% by weight) composed of unsaturated C18 fatty acids, i.e. selected from oleic acid, linolenic acid and linoleic acid, and a mixture of these acids. Triglycerides are preferred. More preferably, whether it is a synthetic source or a natural source (such as sunflower vegetable oil or rapeseed oil), the fatty acid used is composed of oleic acid of more than 50% by weight, more preferably more than 80% by weight. In a specific embodiment of the present invention, the liquid plasticizer is dioctyl phthalate DOP.

[0137] I-4, various additives

[0138] The bio-friendly rubber composition according to the present invention may also contain all or part of the standard additives usually used in rubber compositions intended for the manufacture of shoe outsoles, especially snow boot outsoles, fillers other than those mentioned above, such as non-reinforcing fillers (such as calcium carbonate) or layered materials (such as kaolin and hydrotalcite), pigments, aging protective agents (such as anti-ozone waxes, chemical anti-ozonants, anti-thermal oxidation protective agents), crosslinking systems based on sulfur and sulfur donors and / or peroxides and / or bismaleimides, vulcanization accelerators or anti-reversion vulcanization agents and vulcanization activators.

[0139] The vulcanizing agent is a crosslinking system based on sulfur and sulfur donors and / or peroxides and / or bismaleimide, preferably sulfur, with a weight fraction of preferably 1.4 phr; in a specific embodiment of the present invention, sulfur is produced by Chaoyang Mingyu Chemical Co., Ltd. with a brand name of S200.

[0140] The sulfonamide type accelerator is selected from one or more of N-dicyclohexyl-2-benzothiazole sulfonamide (abbreviated as "CBS"), N-tert-butyl-2-benzothiazole sulfonamide (abbreviated as "TBBS"), N,N-dicyclohexyl-2-benzothiazole sulfonamide (abbreviated as "DCBS"), and N-oxydiethylene-2-benzothiazole sulfonamide (abbreviated as "NOBS"), and the weight proportion is preferably 1.6 phr; in a specific embodiment of the present invention, the sulfonamide type accelerator is produced by Flexsys and the brand is Santocure CBS.

[0141] The aging protection agent is N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (abbreviated as "6PPD"), N,N'-xylyl-p-phenylenediamine (abbreviated as "DTPD"), N-(1,4-dimethylpentyl)-N'-phenyl-p-phenylenediamine (abbreviated as "7PPD"), and N-(1-methylbutyl)-N'-phenyl-p-phenylenediamine (abbreviated as "8PPD"). In a specific embodiment of the present invention, the aging protection agent is produced by Flexsys and its brand is Santoflex@6PPD.

[0142] The antioxidant is a rubber protective wax, preferably 1.5 phr by weight; in a specific embodiment of the present invention, the antioxidant is an anti-ozone wax, specifically a mixture of microcrystalline wax and paraffin wax, produced by RheinChemie, with the brand name Rhein wax 111;

[0143] The rubber accelerator is diphenylguanidine and tetrabenzylthiuram disulfide, and the weight proportion is preferably 2phr; in a specific embodiment of the present invention, the rubber accelerator is produced by Flexsys Company and the brand is Perkacit DPG.

[0144] According to the present invention, adding a vulcanizing agent can make the rubber material change from a linear structure to a three-dimensional mesh structure to enhance the overall performance of the outsole, and can ensure that the sole has sufficient elastic recovery ability in daily walking and exercise, thereby improving the wearing comfort; adding fillers such as carbon black can improve the hardness, strength and wear resistance of the outsole, increase the friction between the sole and the ground, and thus improve the wear resistance of the outsole. In addition, when using a combination of an appropriate amount of fillers (such as calcium carbonate) and plasticizers (such as dioctyl adipate), the former can adjust the rubber hardness and prevent the sole from being too soft; while the latter can make up for the problem of decreased flexibility caused by calcium carbonate filling. The combination of the two can make the sole improve its flexibility at low temperatures while maintaining a certain strength and wear resistance. In the actual formula, the amount of calcium carbonate can be 30-50 parts, and the amount of dioctyl adipate is 10-20 parts. Among them, the main components that affect the low temperature performance of the outsole of shoes and boots include rubber types, plasticizers and fillers. For example, styrene-butadiene rubber and cis-1,2-butadiene rubber in synthetic rubber have lower glass transition temperatures than natural rubber, and their flexibility at low temperatures is inherently good. The cellulose gel introduced in the present invention can improve the low-temperature performance of the outsole of snow boots. Since the cellulose gel has a three-dimensional network structure and abundant hydroxyl groups, its three-dimensional structure plays a role similar to physical cross-linking in the rubber matrix on the one hand, providing rubber finishing strength; on the other hand, it can form hydrogen bonds and other interactions with the rubber molecular chains, limiting the excessive aggregation of the rubber molecular chains, and regulating the glass transition temperature of the rubber to a certain extent, thereby maintaining the flexibility of the rubber.

[0145] In at least one embodiment of the present invention, the Shore A hardness of the rubber composition is in the range of 50 to 70, in particular 55 to 65, and the Shore A hardness of the cured composition is evaluated according to standard ASTM D2240-86.

[0146] I-5. Preparation of rubber composition

[0147] The present invention provides a method for preparing the rubber composition described in any one of the above, comprising the following steps:

[0148] 1) premixing the diene elastomer, the polar elastomer, the reinforcing filler, the silane coupling agent, the hydrocarbon resin, the liquid plasticizer, the aging protective agent and the antioxidant in a closed container, collecting and cooling the obtained mixture;

[0149] 2) adding the vulcanizing agent, the sulfonamide type accelerator and the rubber accelerator into the mixture for mixing and cross-linking to obtain the rubber composition.

[0150] In at least one embodiment of the present invention, the entire mixing includes a first stage premixing and a second stage mixing crosslinking; the first stage premixing is stopped when the container is heated to a maximum temperature of 110°C to 190°C and cooled, preferably 130°C to 180°C, and the first stage premixing time is 3 to 15 minutes; in at least one embodiment of the present invention, the initial container temperature is about 60°C, and then a thermomechanical operation (non-production stage) is performed in this stage, which is maintained for a total of about 5 minutes until a maximum "discharge" temperature of 165°C is reached; cooled to a temperature below 100°C; the second stage (production stage) mixing rubber is heated to below 110°C, preferably 40°C to 100°C, more preferably 40°C to 90°C; the second stage mixing crosslinking time is 5 to 12 minutes; in at least one embodiment of the present invention, a vulcanizing agent and a vulcanization accelerator are added to a mixer (both with a kneader) at 110°C, so that the entire mixture (production stage) is crosslinked within a suitable time selected in combination with the rheometer test results.

[0151] In a specific embodiment of the present invention, Figure 4 As shown, the above preparation is carried out in the following manner:

[0152] 1) Elastomers, silica, modified cellulose, coupling agents, plasticizers and various other ingredients except the crosslinking system are continuously introduced into an internal mixer (final filling ratio: about 70% volume %), the initial container temperature of which is about 60° C. Then a thermomechanical operation is carried out in this stage (non-productive stage), which is maintained for a total of about 5 minutes until a maximum "discharge" temperature of 165° C. is reached;

[0153] 2) The mixture thus obtained is collected and cooled, and then a vulcanizing agent and a vulcanization accelerator are added in a mixer (kneader) at a temperature below 110° C. to allow the entire mixture (production stage) to be crosslinked within a suitable time (mixing time between 5 and 12 minutes).

[0154] In the fifth part, the present invention provides a snow boot outsole, which is made of any of the above-mentioned rubber for snow boot outsole. In particular, the snow boots include hiking snow boots, skiing snow boots, urban snow boots, work snow boots, children's snow boots, and military snow boots.

[0155] All percentages (%) indicated in the present invention are % by weight. The abbreviation "phr" stands for parts by weight per hundred parts of elastomer (or total elastomer if a tree elastomer is present). All values ​​of glass transition temperature "Tg" are measured in a known manner by DSC (Differential Scanning Calorimetry) according to standard ASTM D3418 (1999).

[0156] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0157] The methods used in the following examples, unless otherwise specified, are all conventional methods, carried out according to the techniques or conditions described in the literature in the art or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0158] In the following examples, cellulose formate comes from Qingdao Institute of Bioenergy and Bioprocess Technology, Chinese Academy of Sciences, and its raw materials come from bleached wood pulp, wood fiber raw materials or industrial and agricultural waste biomass, with a degree of substitution of 1.0-2.0, a crystal form of cellulose II, and a degree of polymerization of 300-1000.

[0159] In the aqueous solution of the following binary inorganic salt system AlCl3 / ZnCl2, Al 3+ :Zn 2+ Taking the molar ratio of 0.1:0.9 and the hydration amount of 4 as an example, the preparation steps are as follows: 1) Determine the composition ratio: According to the test requirements, determine the molar ratio of AlCl3 and ZnCl2. In the binary inorganic salt system, the aqueous solution of AlCl3 and ZnCl2 is based on Al 3+ :Zn 2+ Different molar ratios were used to prepare binary inorganic salt aqueous solutions with different hydration amounts. 2) Calculate the required mass: Calculate the weight of each component, assuming a total concentration of 0.1 mol / L, Al 3+ and Zn2+ The molar ratio is 1:9, then the concentration of AlCl3 is 0.01mol / L, and the concentration of ZnCl2 salt is 0.09mol / L. The molar mass of AlCl3 is 133.34g / mol; the molar mass of ZnCl2 is 136.32g / mol. The mass of AlCl3 required is 0.1mol / L*0.1L*133.34g / mol=1.3334g; the mass of ZnCl2 required is 0.9mol / L*0.1L*136.32g / mol=12.269g; 3) Weighing reagents: Use an analytical balance to weigh the required mass of AlCl3 and ZnCl2 respectively. 4) Dissolving: Add the weighed AlCl3 and ZnCl2 into a clean beaker. Then add deionized water to the beaker with different hydration amounts (molar ratio 1:3, 1:4, 1:5), stir with a magnetic stirrer until completely dissolved, and prepare different AlCl3 / ZnCl2 aqueous solutions. If the salt cannot be completely dissolved, it can be heated slightly (not exceeding 60°C), and overheating should be avoided to prevent the salt from decomposing. 5) Mixing: Combine the dissolved AlCl3 and ZnCl2 solutions into a beaker. Continue to stir with a magnetic stirrer to ensure that the two salts are fully mixed. 6) Storage: Transfer the prepared solution to a clean reagent bottle, label it, indicate the solution composition, concentration, date and other information, and store it in a cool and dry place away from direct sunlight. Through the above steps, the hydration solution except AlCl3 / ZnCl2 can be successfully prepared to ensure its stability. If further adjustment and optimization are required, appropriate adjustments can be made according to specific experimental needs.

[0160] The sources of the raw materials in Table 1 of the following examples are as follows:

[0161] BR represents polybutadiene rubber, in which the cis-1,4-bond content is 93%, and is BR9000 produced by PetroChina Daqing Petrochemical Company;

[0162] SBR represents styrene-butadiene rubber (butadiene-styrene copolymer), wherein Tg is -65°C, styrene content is 15%, 1,2-bond content (mol %) of the butadiene part is 24%, and it is NS612 produced by Zeon Co., Ltd., and the butadiene part is at the end of the elastomer chain, with a silanol functional group at one end;

[0163] SBR1 represents styrene-butadiene rubber (butadiene-styrene copolymer), wherein Tg is -65°C, styrene content is 15%, 1,2-bond content (mol %) of the butadiene part is 24%, and it is NS712 produced by Zeon Co., Ltd., and the butadiene part is at the end of the elastomer chain, and both ends have silanol functional groups;

[0164] NBR means acrylonitrile-butadiene rubber (acrylonitrile-butadiene copolymer), wherein the acrylonitrile content is 26-28%, and is NBR 1072 produced by Nandi Chemical Co., Ltd.;

[0165] Carbon black was produced by Cabot Corporation with the brand name N234;

[0166] SiO2 is produced by Rhodia, with the brand name Zeosil 1165MP;

[0167] Cellulose formate was provided by Qingdao Institute of Bioenergy and Process Technology, Chinese Academy of Sciences;

[0168] The modified C5 / C9 copolymer resin is produced by ExxonMobil and is branded as OpperaTM PR 383;

[0169] DOP is dioctyl phthalate produced by Zhejiang Weibo Chemical Technology Co., Ltd., and the brand name is dioctyl phthalate.

[0170] The antioxidant is rubber protective wax, and the anti-ozone wax is a mixture of microcrystalline wax and paraffin produced by RheinChemie with the brand name Rhein wax 111.

[0171] The aging protective agent is N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, produced by Flexsys Company, and the brand name is Santoflex@6PPD.

[0172] The rubber accelerator DPG is diphenylguanidine produced by Flexsys Company with the brand name Perkacit DPG.

[0173] The sulfenamide type accelerator is N-dicyclohexyl-2-benzothiazole sulfenamide produced by Flexsys Company with the brand name Santocure CBS.

[0174] The sulfur was sulfur powder produced by Chaoyang Mingyu Chemical Co., Ltd. with the brand name S200.

[0175] Example 1

[0176] This embodiment provides a method for preparing a modified cellulose powder material, and the specific steps are as follows:

[0177] Step 1: Disperse 1 g of cellulose formate in 1000 mL of a binary inorganic salt system consisting of AlCl3, ZnCl2 and water (Al 3+ :Zn 2+ The molar ratio is 0.1:0.9, the hydration amount is 4), stirred evenly, and ultrasonicated for 2h to obtain an aqueous dispersion of cellulose formate;

[0178] Step 2: Add 6 g of coupling agent Si75 into 100 ml of ethanol, mix evenly, then drop cellulose formate aqueous dispersion into the mixture, heat to 80° C. under stirring, and react for 2 h to obtain cellulose formate-coupling agent dispersion;

[0179] Step 3, centrifugally degas the cellulose formate-coupling agent dispersion, place it in a deionized water coagulation bath and fumigate it for 2 hours to obtain a regenerated cellulose hydrogel; wash the prepared regenerated cellulose hydrogel with deionized water for 60 minutes; then wash and precipitate with water (discard the supernatant, repeatedly add water to wash and precipitate, and finally centrifuge and discard the supernatant) to obtain a cellulose regenerated hydrogel;

[0180] Step 4, placing the cellulose regenerated hydrogel obtained in step 3 in a vacuum tank, evacuating to a vacuum degree of -0.05 to 0.05 MPa at room temperature, then flushing with nitrogen to normal pressure, and then evacuating to a vacuum degree of -0.05 to -0.01 MPa at 0 to 5°C, repeating the steps of flushing with nitrogen and evacuating 3 to 4 times;

[0181] Step 4: Freeze the vacuum-treated modified cellulose hydrogel with liquid nitrogen at a temperature of -24°C to -80°C for 3 hours.

[0182] Step 5: vacuum-drying the quick-frozen cellulose gel to obtain a modified cellulose powder material.

[0183] Example 2

[0184] This embodiment provides a rubber composition for snow boot outsoles and a preparation method thereof. The specific formula is shown in C4 in Table 1. The specific preparation steps are as follows:

[0185] 1) premixing a diene elastomer (polybutadiene BR9000, NS712), a polar elastomer (NBR1072), a reinforcing filler (carbon black N234, white carbon Zeosil 1165MP), a coupling agent (Si-69), a hydrocarbon resin (modified C5 / C9 copolymer resin, PR383) and a liquid plasticizer (dioctyl phthalate), an anti-ozonation wax (Rheinwax 111), and an antioxidant (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) in a closed mixer (filling ratio: about 70% volume %), with an initial container temperature of about 60° C., for a total of about 5 minutes, until a maximum "discharge" temperature of 165° C. is reached, and the obtained mixture is collected and cooled;

[0186] 2) Add a vulcanizing agent (sulfur), a sulfonamide-type accelerator (N-dicyclohexyl-2-benzothiazolesulfonamide) and a rubber accelerator (DPG) into a mixer at a temperature below 110° C., and crosslink the entire mixture (about 4.5 minutes in this embodiment) to obtain a rubber composition.

[0187] Example 3

[0188] The preparation steps were the same as in Example 1, except that the raw materials and composition were replaced with C5 in Table 1.

[0189] Comparative Example 1

[0190] The preparation steps are similar to those of Example 1, except that the raw materials and composition are replaced by T1 in Table 1.

[0191] Comparative Example 2

[0192] The preparation steps are similar to those of Example 1, except that the raw materials and composition are replaced by C1 in Table 1.

[0193] Comparative Example 3

[0194] The preparation steps are similar to those of Example 1, except that the raw materials and composition are replaced by C2 in Table 1.

[0195] Comparative Example 4

[0196] The preparation steps are similar to those of Example 1, except that the raw materials and composition are replaced by C3 in Table 1.

[0197] Table 1 Raw materials and composition of examples and comparative examples (parts by weight, phr)

[0198]

[0199]

[0200] Performance Testing

[0201] The rubber compositions of the above examples and comparative examples were made into snow boot outsoles, and the following properties were tested respectively:

[0202] 1. The wet friction coefficient is tested according to the standard GB / T 3903.6-2017 (test shoe size 255, the experimental medium is grade 3 water, and the test interface is ceramic tile).

[0203] 2. Wear scars: tested according to standard GB / T 9867-2008 method A on non-rotating specimens.

[0204] 3. Low temperature performance: According to the standard GB / T 6031-1998 method, the hardness value should not exceed 20IRHD compared with the hardness at room temperature. In a freezing device or after freezing treatment, the hardness should not exceed 95IRHD. The test sample is the outer sole and heel test sample or the entire sole and heel of the boot, which is placed in a suitable equipment of the manufacturer at a temperature of (-25±)℃ and a pressure of 3h.

[0205] The results are shown in Table 2, wherein T1 and C1-C5 in Table 2 are consistent with those in Table 1.

[0206] Table 2. Performance test results of embodiments and comparative examples

[0207] Footwear T1 C1 C2 C3 C4 C5 Wear marks 100 140 150 86 120 130 Wet friction coefficient 100 115 135 115 120 170 Low temperature performance 100 106 105 100 106 105

[0208] (The unit of the performance parameter wear scar in Table 2 is mm. The higher the coefficient, the better the wear resistance. The low temperature performance in Table 2 is the hardness change. The higher the coefficient, the better the low temperature performance.)

[0209] The friction coefficients of the snow boot outsoles of formulations C4 and C5 in Table 2 on the wet ceramic surface are 120 and 170 respectively, which are much higher than the reference soles in comparative example T1. This further demonstrates that the use of the modified cellulose powder as a reinforcing filler for rubber can enhance the wear resistance of the rubber.

[0210] From the comparison results of formulations C1 and T1 in Table 2, it can be seen that, compared with the diene elastomer with a single-terminal modified SiOR-functional group, the diene elastomer with a dual-terminal modified SiOR functional group can enhance the wear resistance of the rubber, which enhances the interfacial affinity between silica and rubber and can further improve the dispersion ability of silica in the rubber.

[0211] From the comparison results of formulations C3 and T1 in Table 2, it can be seen that when the diene elastomer modified with dual-end SiOR functional groups is combined with ordinary cellulose formate, due to the poor dispersibility of cellulose formate in the rubber matrix, all properties are better, and the wear mark is lower than that of the control example.

[0212] From the comparison results of formulations C4 and T1 in Table 2, it can be seen that the diene elastomer modified with SiOR functional groups at both ends combined with modified cellulose formate can achieve better wear resistance and greatly improve the grip on wet ground without reducing the low temperature performance.

[0213] From the comparison results of formulation C5 and comparative example T1 in Table 2, it can be seen that optimizing the amount of diene elastomer modified with dual-terminal SiOR functional groups can further improve the anti-slip performance of the sole without reducing the low-temperature performance.

[0214] From the comparison results of formulation C5 and formulation C2 in Table 2, it can be seen that after replacing the cellulose formate powder with modified cellulose formate powder, the cellulose formate adsorbs metal ions and the silane modification is conducive to piercing the water film, and the wet friction coefficient of the rubber composition is greatly improved. However, the reinforcement performance of cellulose formate itself is weak, so the wear performance is slightly worse, but the overall effect is better.

[0215] In summary, based on the traditional rubber sole, the present invention adopts modified cellulose powder as the reinforcing material of rubber, and combines it with components such as diene elastomer and plasticizer system to prepare the rubber material. The obtained rubber sole has excellent anti-slip performance, wear resistance and rubber low-temperature performance, and is a biological and environmentally friendly rubber composition.

[0216] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, can implement the present invention in a wider range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principle of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departing from the disclosed scope in the application and the changes made with conventional techniques known in the art.

Claims

1. A method for preparing rubber-modified cellulose powder for snow boot outsoles, characterized in that: The steps include: S1, dispersing cellulose formate in a binary inorganic salt system consisting of AlCl3, ZnCl2 and water to obtain an aqueous dispersion of cellulose formate; S2, dropping the coupling agent solution into the aqueous dispersion of cellulose formate and heating it to obtain a cellulose formate-coupling agent dispersion; S3, placing the cellulose formate-coupling agent dispersion in a coagulation bath of deionized water for fumigation to obtain a regenerated cellulose hydrogel; S4, subjecting the regenerated cellulose hydrogel to vacuum treatment, and then sequentially freezing and vacuum drying to obtain the rubber-modified cellulose powder for the snow boot outsole.

2. The method for preparing the rubber-modified cellulose powder for snow boot outsoles according to claim 1, characterized in that: In step S1, the cellulose formate has a degree of substitution of formate groups on the cellulose molecules of 1.0 to 2.0, and a crystalline form of cellulose II; the degree of polymerization of the cellulose formate is 300 to 1000; The cellulose in the cellulose formate is microcrystalline cellulose, cotton pulp, dissolving pulp, ascidian cellulose or bacterial cellulose; In the binary inorganic salt system, Al 3+ :Zn 2+ : The molar ratio of H2O is (0.1):(0.9):(3.5-5.5), preferably 0.1:0.9:4; The dispersion is carried out at 15 to 30° C. The dispersion is ultrasonic dispersion, preferably ultrasonic dispersion for 0.3 to 3 hours; Each 1g of cellulose formate is dispersed in 1000mL of binary inorganic salt system; The coupling agent is a silane coupling agent, preferably one or a mixture of bis(3-ethoxysilylpropyl)tetrasulfide, bis(3-ethoxysilylpropyl)disulfide, 3-(trimethylsiloxane)-1-propanethiol; The solvent of the coupling agent solution is one or a mixed solvent of ethanol, polypropylene glycol, ethyl acetate, butyl acetate and hexane; The volume ratio of the coupling agent solution to the aqueous dispersion of cellulose formate is 1:10; The heating temperature is 70° C. to 100° C., preferably 80° C., and the heating time is 1 to 10 hours, preferably 2 hours.

3. The method for preparing the rubber-modified cellulose powder for snow boot outsoles according to any one of claims 1 to 2, characterized in that: The fumigation time is 2 to 6 hours; The method further comprises the step of centrifuging and degassing the cellulose solution before gas fumigation; The method comprises the step of washing the regenerated cellulose hydrogel with water after fumigation; The vacuum treatment comprises: 1) evacuating the cellulose regenerated hydrogel at room temperature to a vacuum degree of -0.05 to 0.05 MPa; 2) flushing nitrogen to normal pressure, and then evacuating to a vacuum degree of -0.05 to -0.01 MPa at 0 to 5°C; 3) flushing nitrogen to normal pressure, and then evacuating to a vacuum degree of -0.05 to -0.01 MPa at 0 to 5°C, repeating the steps of flushing nitrogen and evacuating in step 2) 3 to 4 times; The freezing temperature is -24°C to -80°C, and the freezing time is 2 to 4 hours.

4. The rubber-modified cellulose powder for snow boot outsoles obtained by the preparation method according to any one of claims 1 to 3.

5. A rubber composition for snow boot outsoles, characterized in that: The invention is prepared from the following raw materials, measured by weight: 20 to 100 parts of diene elastomer, 0 to 80 parts of polar elastomer, 50 to 120 parts of reinforcing filler, 2 to 40 parts of hydrocarbon resin, 5 to 60 parts of liquid plasticizer, 2 to 20 parts of silane coupling agent, 1.0 to 2.5 parts of vulcanizing agent, 1.0 to 2.5 parts of sulfenamide accelerator, 2 parts of aging protective agent, 1.5 parts of antioxidant and 2 parts of rubber accelerator; The diene elastomer carries at least one SiOR-functional group, R being hydrogen or hydroxyl; The polar elastomer comprises one or more of nitrile rubber, hydrogenated nitrile rubber, and carboxyl nitrile rubber; The reinforcing filler comprises carbon black, SiO2 and the modified cellulose powder material according to claim 4; The glass transition temperature of the hydrocarbon resin is ≥20°C.

6. The rubber composition for snow boot outsoles according to claim 5, characterized in that: The diene elastomer is one or a mixture of two or more of polybutadiene rubber (BR), synthetic isoprene (IR), natural rubber (NR), and butadiene copolymer; the polybutadiene rubber is preferably a polybutadiene rubber having a cis-1,4-bond content greater than 90%; the butadiene copolymer is preferably a butadiene-styrene copolymer having a glass transition temperature of 0°C to -80°C, a styrene content of 5% to 60% by weight, a 1,2-bond molar content of 4% to 75% in the butadiene part, and a trans-1,4-bond molar content of 10% to 80%; In the SiOR functional groups of the diene elastomer, R is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms; the diene elastomer is preferably a diene elastomer modified with SiOR functional groups at both ends; The content of acrylonitrile in the molecular structure of the polar elastomer is greater than 25%; In the reinforcing filler, the mass ratio of carbon black, SiO2 and the modified cellulose powder material is (2-10): (70-120): (5-30); The silane coupling agent is at least a bifunctional organosilane or polyorganosiloxane, preferably a silane polysulfide of the following general formula: Z-A-S X -A-Z(I) In formula (I), x is an integer from 2 to 8 (preferably from 2 to 5); the A symbols, which are the same or different, identify a divalent hydrocarbon group (preferably a C1-C18 alkylene group or a C6-C12 arylene group, more particularly a C1-C10, especially a C1-C4, alkylene group, especially propylene); the Z symbols, which are the same or different, correspond to one of the following three formulae: in: - R1 groups are substituted or unsubstituted and identical or different from each other and represent C1-C18 alkylene, C5-C18 cycloalkyl or C6-C12 arylene (preferably C1-C6 alkyl, cyclohexyl or phenyl, in particular C1-C4 alkyl, more in particular methyl and / or ethyl); -R2 groups are substituted or unsubstituted and identical to or different from each other and represent C1-C18 alkoxy, C5-C18 cycloalkoxy or C6-C12 arylene (preferably C1-C8 alkoxy, C5-C8 cycloalkoxy groups, in particular C1-C4 alkoxy, more in particular methoxy and / or ethoxy).

7. The rubber composition for snow boot outsoles according to any one of claims 5 to 6, characterized in that: The weight ratio of the hydrocarbon resin to the liquid plasticizer is 1:5 to 5:1, preferably 1:4 to 4:1; The weight portion of the hydrocarbon resin is 2 to 40 parts, the weight portion of the liquid plasticizer is 5 to 60 parts, and the total weight portion of the hydrocarbon resin and the liquid plasticizer is 10 to 80 parts; The glass transition temperature of the hydrocarbon resin is ≥25°C, preferably 30°C to 100°C, more preferably 30°C to 95°C; The number average molar mass Mn of the hydrocarbon resin is 400 to 2000 g / mol, preferably 500 to 1500 mol / g; The molecular weight distribution D of the hydrocarbon resin is less than 3, preferably less than 2; The glass transition temperature of the liquid plasticizer is below -20°C, more preferably below -40°C; The liquid plasticizer is selected from one or more of liquid diene polymers, polyolefin oils, paraffin oils, aromatic extract oils, shallow extraction oils, treated aromatic extract oils, rubber aromatic oils, mineral oils, vegetable oils, ester plasticizers, ether plasticizers, phosphate plasticizers, sulfonate plasticizers, and carboxylate plasticizers; The sulfonate plasticizer is preferably one or more of alkyl phenyl sulfonate, sodium benzene sulfinate, and 1,4-butane sultone; The phosphate plasticizer preferably contains between 12 and 30 carbon atoms, more preferably trioctyl phosphate; The carboxylic acid ester plasticizer is preferably one or more of trimellitate, triglyceride, adipate, azelaic acid ester, sebacate, and dioctyl phthalate; The vulcanizing agent is a crosslinking system based on sulfur and sulfur donor and / or peroxide and / or bismaleimide, preferably sulfur; The sulfenamide type accelerator is selected from one or more of N-dicyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, N,N-dicyclohexyl-2-benzothiazole sulfenamide, and N-oxydiethylene-2-benzothiazole sulfenamide; The aging protective agent is one or more of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-xylyl-p-phenylenediamine, N-(1,4-dimethylpentyl)-N'-phenyl-p-phenylenediamine, and N-(1-methylhexyl)-N'-phenyl-p-phenylenediamine; The antioxidant is rubber protective wax; The rubber accelerator is one or more of diphenylguanidine and tetrabenzylthiuram disulfide.

8. The method for preparing the rubber composition for snow boot outsoles according to any one of claims 5 to 7, comprising the following steps: 1) premixing the diene elastomer, the polar elastomer, the reinforcing filler, the silane coupling agent, the hydrocarbon resin, the liquid plasticizer, the aging protective agent and the antioxidant in a closed container, collecting and cooling the obtained mixture; 2) adding the vulcanizing agent, the sulfonamide type accelerator and the rubber accelerator into the mixture for mixing and cross-linking to obtain the rubber composition.

9. The method for preparing the rubber composition for snow boot outsoles according to claim 8, characterized in that: The premix is ​​heated to a maximum temperature of 110°C to 190°C in the container, and then stopped heating and cooled, preferably 130°C to 180°C. The premix is ​​heated for 3 to 15 minutes. The mixing and cross-linking is performed by heating to below 110° C., preferably 40° C. to 100° C., and the heating time for the mixing and cross-linking is 5 to 12 minutes.

10. A snow boot outsole, characterized in that: The invention is made from the rubber composition for snow boot outsoles according to any one of claims 5 to 7 or the rubber composition prepared by the preparation method according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Rubber composition based on silica and a functionalized diene polymer terminated with a silanol group

    EP0778311B1

  • Rubber composition comprising carbon black having silica fixed to its surface and a diene polymer functionalized or modified with silanol groups

    EP0877047B1

  • Tire with component of rubber composition comprised of silanol and / or siloxy functionalized elastomer and silica

    EP1400559B1

  • Tyre and running tread comprising as coupling agent a bis-alkoxysilane tetrasulphide

    WO2002083782A1

  • Tyre tread reinforced with silica having a very low specific surface area

    WO2003002649A1